Persepsi Masyarakat Lokal Dalam Pengembangan Desa Wisata Kaba Kaba - Deswikasari, Wayan Helga; Saputra, I Gede Gian (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p20, 2023)
Tabanan Regency is one of the regions that has developed its tourism sector well. Kaba Kaba Village Tourism is one of the villages with tourist attractions, known for its natural beauty and high historical value. However, there are still some limitations in terms of innovation, exploration, and cooperation from the local village community to develop tourism products. This study aims to assess the existing condition of the development of Kaba Kaba Village Tourism and explore the local community's perception of its development. The research methods employed were observation, interviews, and documentation. The findings of this study indicate a lack of innovation, exploration, and cooperation between the local community and other stakeholders. Therefore, there is a need to enhance the development of tourism products to strengthen the existence of Kaba Kaba Village Tourism, benefiting both the local community and tourists. Keywords: Local Community Perception, Kaba Kaba Tourism Village, Tourist Village Development